Pengaruh Panjang Setek dan Konsentrasi Rootone F Terhadap Pertumbuhan Setek Jarak Pagar (Jatropha curcas L.) - Siti Wahyuni; Dukat .; Meilina Prasetyo (Agrovigor, 2017)
The purpose of this study is to determine the influence of the length of cuttings and concentration Rootone F to growth cuttings jatropha (Jatropha curcas L.). Research methodology used to the experimental method experimental design completely randomized design pattern combination, which consists of 12 factors and repeated three times. A (Length cuttings of 20 cm and a concentration of 0 ppm Rootone F), B (length of cuttings 20 cm and a concentration of 50 ppm Rootone F), C (Length cuttings 20 cm and a concentration of 100 ppm Rootone F), D (Long cuttings 20 cm and concentration 150 ppm Rootone F), E (Long cuttings of 25 cm and a concentration of 0 ppm Rootone F), F (Long cuttings of 25 cm and a concentration of 50 ppm Rootone F), G (Long cuttings of 25 cm and a concentration of 100 ppm Rootone F), H ( long cuttings of 25 cm and a concentration of 150 ppm Rootone F), I (long cuttings of 30 cm and a concentration of 0 ppm Rootone F), J (long cuttings of 30 cm and a concentration of 50 ppm Rootone F), K (length of cuttings 30 cm and a concentration of 100 ppm Rootone F) and L (length 30 cm cuttings and concentration of 150 ppm Rootone F). Variables observed that the number of shoots, number of leaves, fresh weight and root volume.The results showed occurred the length use of cuttings and concentration Rootone F real impact on the number of shoots, number of leaves and root volume. The treatment of length cuttings and concentration Rootone F the number of shoots are significantly at age 7 HST, age 28 HST numbers of leaves and root volume age 56 HST. The results are the best effect on the treatment of cuttings 20 cm and F Rootone concentration of 100 ppm.